Draft Annual Plan 1973-74 (Part-II-Statements) Union Territory of Pondicherry - Planning Commission (Planning Commission, 1972)
Agricultural education- and research Agricultural production Small farmers and agricultural laborers, Minor irrigation Soil conservation Warehousing, marketing and storage Ports and harbors Irrigation and Power Nutrition Programmes Agricultural education and Research Extension, training and farmers' education Manures and fertilizers Ware-housing and storage
Union Territory of Pondicherry
Revenue, Finance and Planning Department Pondicherry
Keywords: Outlay and expenditure; Programme-wise outlay and expenditure; Scheme-wise outlays and expenditure; Important projects costing; Check list in respect of principal projects; Physical targets and achievements; Proposals for advance action for the fifth Plan; Spill-over to the fifth plan; Scheme-vise outlay and expenditure; Scheme-wise physical targets and achievements; sponsored schemes